2005
DOI: 10.1111/j.1467-9590.2005.01565
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of Multihump Vector Solitons in Coupled Nonlinear Schrödinger Equations

Abstract: Spectral stability of multihump vector solitons in the Hamiltonian system of coupled nonlinear Schrödinger (NLS) equations is investigated both analytically and numerically. Using the closure theorem for the negative index of the linearized Hamiltonian, we classify all possible bifurcations of unstable eigenvalues in the systems of coupled NLS equations with cubic and saturable nonlinearities. We also determine the eigenvalue spectrum numerically by the shooting method. In case of cubic nonlinearities, all mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
2
38
0
2
Order By: Relevance
“…In these cases the linearised operators b and c would be of zero order. In models of optical pulse propagation of birefringent fibres and in wavelength-divisionmultiplexed systems they are of the first order (see Pelinovsky and Yang [25]). They may be of higher orders as well, for example in models of optical solitons with higher order effects (see Nakkeeran [24]).…”
Section: This Is the Simplest Example Of Schrödinger Equations Couplementioning
confidence: 99%
“…In these cases the linearised operators b and c would be of zero order. In models of optical pulse propagation of birefringent fibres and in wavelength-divisionmultiplexed systems they are of the first order (see Pelinovsky and Yang [25]). They may be of higher orders as well, for example in models of optical solitons with higher order effects (see Nakkeeran [24]).…”
Section: This Is the Simplest Example Of Schrödinger Equations Couplementioning
confidence: 99%
“…Analytical study of this phenomenon demands a separate consideration and can be performed, for example, by a stability analysis as developed in Ref. [43]. Second, we have restricted ourselves to the study of the adiabatic approximation of the general perturbation theory.…”
Section: Discussionmentioning
confidence: 99%
“…Such a state can be treated as a pair of two ferromagnetic solitons with antiparallel spins [22]. Previous analysis of stability of multi-humped vector solitons for the cubic nonlinearity revealed that they are always unstable [42,43]. Hence, we can suggest that the most likely scenario of the polar soliton evolution under the action of a perturbation would be its splitting into a pair of ferromagnetic solitons.…”
Section: Soliton Solutions a Rank-one Solitonmentioning
confidence: 99%
“…The coupled-NLS system with D 2 ¼ 1 may have multi-hump soliton solutions too, but they are expected to be unstable [25,26]. In this paper, we aim to demonstrate that, for values D 2 < 1, including small negative values of the relative GVD coefficient (i.e., the case of weak normal GVD in the v-component), Eqs.…”
Section: Introduction and The Modelmentioning
confidence: 96%